Foliar anatomy and micromorphology of southern South American Alstroemeriaceae: Alstroemerieae, and its systematic implications in Alstroemeria - Sanso, Andrea Mariel (2014)
Alstroemerieae is an exclusively Central and South American tribe belonging to Alstroemeriaceae, which comprises two large genera, Alstroemeria and Bomarea. Alstroemeria has two areas of distribution, mediterranean Chile and central southeastern Brazil. Most Bomarea species grow in forests and hedges in moist areas, however, some species are adapted to dry Andean valleys and high altitudes. Previous leaf anatomical data were obtained from a limited group of species. To assess the value of the anatomical characters for the systematics and their importance as adaptations to different environments, we compared representative species from different geographical areas and habitats. Data regarding leaf anatomy and micromorphology were obtained from light microscopy and scanning electron microscopy and were combined with macromorphology for 27 Alstroemerieae species. In accordance with earlier studies, our results show variation in relation to several leaf morpho-anatomical characters. Based on these we define seven types. We furthermore analyzed the morpho-anatomical characters in a phylogenetic context. Morpho-anatomical characters are highly homoplastic within the family. Leaf anatomy may support monophyly of Baker's informal grouping of Alstroemeria Brazilian species with rigid leaves, however, a more thorough study of Brazilian Alstroemeria species are needed to confirm this.